Impact of Two Different Reference Measurement Procedures on Apparent System Accuracy of 18 CE-Marked Current-Generation Blood Glucose Monitoring Systems. (September 2022) - Freckmann, Guido; Baumstark, Annette; Jendrike, Nina; Mende, Jochen; Schauer, Sebastian; Link, Manuela; Pleus, Stefan; Haug, Cornelia
Background: Measurement accuracy has been assessed for many different blood glucose monitoring systems (BGMS) over the years by different study groups. However, the choice of the comparison measurement procedure may impact the apparent level of accuracy found in such studies. Materials and Methods: Measurement accuracy of 18 different BGMS was assessed in a setting based on ISO 15197 using two different comparison methods in parallel: a glucose oxidase (GOD)-based and a hexokinase (HK)-based method. Accuracy limits of ISO 15197 were applied, and additional analyses were performed, including bias, linear regression, and mean absolute relative difference (MARD) to assess the impact of possible differences between comparison methods on the apparent level of accuracy. Results: While ≈80% of BGMS met the accuracy criteria of ISO 15197 when compared with the respective manufacturers' reference measurement procedure, only two-thirds did so against both comparison methods. The mean relative bias ranged from −6.6% to +5.7% for the analysis against the GOD-based method and from −11.1% to +1.3% for the analysis against the HK-based method, whereas MARD results ranged from 3.7% to 9.8% and from 2.3% to 10.5%, respectively. Results of regression analysis showed slopes between 0.85 and 1.08 (GOD-based method) and between 0.81 and 1.01 (HK-based method). Conclusions: The results of this study indicate that there are systematic differences between the reference measurement procedures used for BGMS calibration as well as for system accuracy assessment. Because of the potential impact on therapy of patients with diabetes resulting from these differences, further steps toward harmonization of the measurement procedures' results are important.